Production and Evaluation of Yoghurt Produced from Tiger Nut Enriched with Cinnamon - Oladotun Olakanmi OGUNTOYINBO; Olumuyiwa Adekanmi BABARINSA; Ibijoke Itunu OTESILE (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
This study evaluated the quality characteristics of yoghurt produced from tiger nut milk enriched with cinnamon. Valued for their high nutritional content, tiger nuts were combined with cinnamon at varying ratios (100:0, 99.5:0.5, 99:1, 98.5:1.5, and 98:2) to enhance yoghurt quality. Proximate composition, pH, titratable acidity (a measure of the yoghurt's acidity level), Brix content (a measure of the yoghurt's sugar concentration), mineral levels, and antinutrient concentrations (such as tannins, phytates, oxalates, and saponins—compounds that can inhibit nutrient absorption) were analyzed across formulations. Sensory evaluations were conducted by trained panelists. Results showed moisture content ranging from 83.75% to 86.25%, crude protein 2.06% to 2.11%, crude fat 2.00% to 3.50%, ash 0.28% to 0.40%, and carbohydrates 8.35% to 11.69%. pH values were 4.47 to 5.22, titratable acidity 0.09% to 0.11%, and Brix content 8.00 to 8.03. The 98:2 sample exhibited the highest mineral content, particularly in phosphorus, potassium, sodium, iron, and zinc. Antinutrients remained within safe limits: tannins (0.13–0.51 mg/ml), phytates (0.44–0.66 mg/ml), oxalates (0.12–0.13 mg/ml), and saponins (0.07–0.25 mg/ml). Sensory analysis revealed significant improvements in taste, aroma, and overall acceptability with increased cinnamon. The 98:2 ratio were the most preferred, highlighting cinnamon's role in enhancing flavor and sensory appeal. The study concludes that cinnamon-enriched tiger nut yoghurt is a nutritionally functional, sensory-appealing product with safe antinutrient levels and potential health benefits.